2012
DOI: 10.1186/1471-2474-13-209
|View full text |Cite
|
Sign up to set email alerts
|

The value of high-frequency and color Doppler ultrasonography in diagnosing congenital muscular torticollis

Abstract: Background: Congenital muscular torticollis (CMT) is a relatively common neck deformity in infancy. The aim of our research was to determine the value of high-frequency and color Doppler ultrasonography in diagnosing CMT. Methods: Patients with a clinical suspicion of CMT underwent an ultrasound examination before diagnosis, and the sonographic characteristics were analyzed and compared with the clinical findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…This method is characterized by high sensitivity and specificity of 95.83% and 83.33%, respectively. The ultrasonographic findings vary in accordance with different CMT stages [18].…”
Section: Diagnosismentioning
confidence: 80%
“…This method is characterized by high sensitivity and specificity of 95.83% and 83.33%, respectively. The ultrasonographic findings vary in accordance with different CMT stages [18].…”
Section: Diagnosismentioning
confidence: 80%
“…Two‐dimensional US has been applied for CMT diagnosis and been used to confirm the differential diagnosis of children's neck masses . Wang et al evaluated the value of high‐frequency and color Doppler US in the diagnosis of CMT. They found that different stages of CMT had different echogenicity characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…Two‐dimensional (2D) ultrasound (US) imaging, conducted with high‐resolution linear array transducers, has been applied in the assessment of tissue fibrosis in musculoskeletal disorders . To date, studies using 2D B‐mode US to assess the severity of fibrosis of the SCM and its relationship with the activity of neck rotation have been conducted by multiple research centers . Although these data revealed a good correlation between 2D B‐mode US and the activity of neck rotation and the degree of fibrosis of the SCM, the use of B‐mode US yielded sensitivity of only 67% to 81% for the detection of neuromuscular disorders in children .…”
mentioning
confidence: 99%
“…Asymmetry and skull deformities are more often seen in adult cases. It can help to define the stage of the disease for a better treatment choice [5]. Magnetic resonance imaging can also be useful by showing fibrosis and muscle atrophy [2].…”
Section: Discussionmentioning
confidence: 99%